2015
DOI: 10.1016/j.drugpo.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Social and recovery capital amongst homeless hostel residents who use drugs and alcohol

Abstract: Homeless hostel residents who use drugs and alcohol have various opportunities for building social capital that can in turn foster recovery capital. Therapies that focus on promoting positive social networks amongst people experiencing addiction seem to offer a valuable way of working with homeless hostel residents who use drugs and alcohol. Gains are, however, likely to be maximised where hostel management and staff are supportive of, and actively engage with, therapy delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Once homeless, individuals have trouble forming connections that meet their social needs (Neale & Brown, ). Although networks develop between homeless people, these are often small (Gray, Shaffer, Nelson, & Shaffer, ; Neale & Stevenson, ) and marked by forced conviviality (Snow & Anderson, ), indicating relationships may lack depth necessary to foster belonging. Furthermore, homelessness itself is a distressing and—some have argued—traumatic experience that may result in distrust and disconnection with others (Goodman, Saxe, & Harvey, ; Johnson & Chamberlain, ) potentially undermining development of connections during homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Once homeless, individuals have trouble forming connections that meet their social needs (Neale & Brown, ). Although networks develop between homeless people, these are often small (Gray, Shaffer, Nelson, & Shaffer, ; Neale & Stevenson, ) and marked by forced conviviality (Snow & Anderson, ), indicating relationships may lack depth necessary to foster belonging. Furthermore, homelessness itself is a distressing and—some have argued—traumatic experience that may result in distrust and disconnection with others (Goodman, Saxe, & Harvey, ; Johnson & Chamberlain, ) potentially undermining development of connections during homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the familiar atmosphere at the medical respite care centre created a safe environment, which enabled more focus on recovery. These findings are supported by a study from the UK that found relations to family, social workers and other hostel residents to boost the social and recovery capital among homeless people (Neale & Stevenson, ). Nevertheless, Neale et al.…”
Section: Discussionmentioning
confidence: 55%
“…Such support is pivotal in helping those in recovery to manage their addiction(s) and maintain abstinence (Litt et al 2009;Stevens et al 2010). It also provides emotional and practical support (Neale 2001;Neale and Stevenson 2015) and enables individuals to belong to a group, thus fostering social identity (Best et al 2010;Buckingham et al 2013;Pagano et al 2013). …”
Section: The Role Of Recovery Capitalmentioning
confidence: 99%
“…Being part of a group and fostering a social identity supports recovery (Best et al 2010;Buckingham et al 2013;Kaplan et al 2010;Pagano et al 2011Pagano et al , 2013. There is an inverse association between positive peer support networks and recovery relapse (Litt et al 2009;Moos 2008;Neale and Stevenson 2015;Panebianco et al 2016;White 2009). Peer support offers opportunities to adopt more positive social norms that can promote engagement in enjoyable non-substance-related activities, and which may override the norms of pro-drug use networks (Laudet et al 2004;Longabaugh et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation